Effectiveness of fractionated microneedle radiofrequency in treatment of seborrheic dermatitis - Anwar Issa Hasan; Ethar Falah Hasan; Tuqa Mohammed Latif (Medical Journal of Babylon)
Abstract Introduction: Seborrheic dermatitis (SD) is a chronic, relapsing skin illness that causes erythematous, scaly patches and plaques on sebaceous-rich regions including the scalp, face, and chest. Fractionated microneedle radiofrequency (FMR) manages SD symptoms, reduces inflammation, controls sebum production, and improves skin quality and appearance, increasing patient satisfaction. Objective: The aim of this research is to determine the effectiveness of FMR in treating SD. Materials and Methods: Cross-sectional study. Group A included 20 SD patients. They are treated with combination medicine therapy (isotretinoin pill 10 mg on alternative days with topical emollient cream) and FMR single section each month, with an average of two sections per patient (1–4 section). Group B included 20 SD patients. Group B received isotretinoin tablets of 10 mg on alternative days and a topical emollient cream. Results: Group A (mean age = 31.5 ± 7.6 years, 25% females, 75% males) showed a greater reduction in SD grades after treatment compared to group B (mean age = 31.6 ± 8.7 years, 35% females, 65% males). Group A also had a higher percentage of non-relapsing SD cases (63%) and higher satisfaction levels (73.7%) post-treatment, with no significant association between gender, age, and satisfaction. Clear SD grade correlated with higher satisfaction (72.7%) and lower relapse rates (81.1%). Conclusion: FMR and topical therapy dramatically decrease SD severity and recurrence rates, with excellent patient satisfaction across all ages and genders. These encouraging outcomes need larger studies.